Memory and Representation of Individual Identity in the Novels of Samira Al-Mana - Manaf Dawood, Researcher. Zainab; Abdul-Hussein Khalaf, Prof. Dr. Aqeel (Basra studies journal, 2024)
This research examines the role of memory in shaping individual identity in the novels of Iraqi writer Samira Al-Mana. The selection of Al-Mana's works is driven by their thematic exploration of identity representation within cultural studies. Her narratives provide insights into cultural contexts by depicting historical, social, political, and religious events, portraying Iraqi reality and the experience of exile. Spanning from the political upheavals and societal structures of the 1970s to the post-regime era, the study focuses on how memory formation and cultural influences create a nuanced understanding of the past to address contemporary issues. This dynamic process leads to a struggle between multiple identities, whether rooted in personal environments or transformed through engagement with other societies, thereby defining individual identity.